Principal-investigator-led missions in the space sciences (National Academies Press, 2006)
Principal Investigator-Led (PI-led) missions are an important element of NASA's space science enterprise. While several NRC studies have considered aspects of PI-led missions in the course of other studies for NASA, issues facing the PI-led missions in general have not been subject to much analysis in those studies. Nevertheless, these issues are raising increasingly important questions for NASA, and it requested the NRC to explore them as they currently affect PI-led missions. Among the issues NASA asked to have examined were those concerning cost and scheduling, the selection process, relationships among PI-led team members, and opportunities for knowledge transfer to new PIs. This report provides a discussion of the evolution and current status of the PI-led mission concept, the ways in which certain practices have affected its performance, and the steps that can carry it successfully into the future. The study was done in collaboration with the National Academy of Public Administration.